Drawing Perspective. - Fisher, Tim (Search Press, Limited, 2021)
"...By far the best primer [on perspective] I've ever seen. If you have other books, throw them away and buy this. You won't regret it." - Artbookreview.net Learn how to master perspective and create convincing drawings of the three-dimensional world with the help of artist and teacher, Tim Fisher. Every aspect of perspective, from zero- to multi-point, is explored and explained in simple terms that everyone can understand. In addition to landscapes and buildings, you will learn how to apply perspective to people, animals, boats, reflections and more. There is also expert advice on drawing curved objects and inclined planes, a run-down of common mistakes, and an inspirational chapter on moving beyond a rigid application of the rules to draw freely and instinctively. Clear diagrams and finished drawings are included throughout, along with numerous exercises so that you can put your new skills into practice. This is a revitalized edition of Drawing Masterclass: Perspective (ISBN: 9781782211112).
Keywords: Perspective.; Drawing -- Technique.; elektronické knihy; electronic books